A novel multi-reaction microdroplet platform for rapid radiochemistry optimization. Issue 35 (1st July 2019) - Rios, Alejandra; Wang, Jia; Chao, Philip H.; van Dam, R. Michael
Abstract : Multi-reaction microdroplet chip enables rapid radiotracer optimization for positron emission tomography. Abstract : During the development of novel tracers for positron emission tomography (PET), the optimization of the synthesis is hindered by practical limitations on the number of experiments that can be performed per day. Here we present a microliter droplet chip that contains multiple sites (4 or 16) to perform reactions simultaneously under the same or different conditions to accelerate radiosynthesis optimization.